Impact of solid fuel usage on respiratory symptoms among reproductive aged women: a cross-sectional study in Sri Lanka - Malshani Lakshika Pathirathna; Chandraratne Mahinda Bandara Dematawewa; Kayako Sekijima; Mieko Sadakata; Yoshiyuki Muramatsu; Naoshi Fujiwara (BMC, 2022)
Abstract Background Worldwide, around 3 billion people rely on solid fuel for their daily energy needs. Household air pollution secondary to solid fuel burning is a major risk factor for respiratory mobility among vulnerable populations. This study aimed to investigate the respiratory symptoms associated with solid fuel usage, the level of kitchen fuel smoke exposure and its association with respiratory symptoms among reproductive-aged women in Sri Lanka, where most households exclusively use firewood as the primary cooking fuel. Methods A descriptive cross-sectional study was conducted among 403 reproductive-aged women (15 to 49 years) in the Central Province, Sri Lanka. A structured interviewer-administered questionnaire was used to collect data, and an exposure assessment was done using a breath carbon monoxide monitor. Results After adjusting for potential confounding factors by the logistic regression models, the odds ratios (OR) of the liquid petroleum gas-only users for at least one respiratory symptom relevant to cough (OR: 0.39; 95% confidence interval [CI]: 0.20-0.78), wheezing (OR: 0.47; 95% [CI]: 0.26-0.87), and dyspnea (OR: 0.44; 95% CI: 0.24-0.84) were significantly lower compared to firewood-only users. The mean of expired air carbon monoxide and estimated carboxyhemoglobin levels of liquid petroleum gas-only users (2.84 ± 2.85 ppm; 1.08 ± 0.46%) were significantly lower than those of firewood-only users (5.27 ± 4.64 ppm; 1.47 ± 0.74%). Conclusions The use of firewood increased the risk of respiratory symptoms among reproductive-aged women in Sri Lanka. Health education focused on positive behavioral changes and effective and efficient clean energy policies are recommended to mitigate the risk associated with solid fuel smoke exposure.